Cosmopolis or the New Jerusalem Modern Social Imaginaries and the Catholic University - Muldoon, Tim (2016)
Charles Taylor's exploration of modern social imaginaries sheds light on the differing ways that university faculty and leaders today reflect and help shape the world. This article examines Taylor's work as a point of departure for suggesting two contrasting models of social imaginary abroad in university education-namely, cosmopolis and new Jerusalem. It explores what a robust Catholic imagination represented by the latter model might mean for the contemporary Catholic university, especially as regards the desire for integration of knowledge that is truly reflective of the term "university." It pays particular attention to Bernard Lonergan's notion of cosmopolis as a way of imagining anew the ways that Catholic universities form students and contribute to research and scholarship, and emphasizes the task of faculty formation as central to Catholic mission in the academy.
Keywords: cosmopolis; Epistemology; Social Imaginaries; University